Exploring Cash Waqf Potential and Management Models for Muslim Economic Development - Aryanti, Yosi; Bustamar, Bustamar; Jaafar, Azhar (IKONOMIKA, 2025)
This research aims to explore potential sources of cash waqf and financial management models to support economic development among Muslim communities in West Sumatra, Indonesia. Using a qualitative phenomenological approach, data were collected through in-depth interviews with seven purposively selected informants and direct field observations. Analysis employed the Miles & Huberman interactive thematic model. Findings reveal three promising sources of cash waqf: contributions from prospective brides and grooms, State Civil Service employees, and student movements at primary to senior secondary levels. These sources are estimated to generate approximately Rp. Rp. 53,527,824,000 annually. The funds are managed through mudharabah concepts and allocated to four economic initiatives: micro, small, and medium enterprise capital assistance, palm oil plantation development, catfish farming, and cattle breeding. The study recommends expanding cash waqf participation across broader segments of society, including entrepreneurs, farmers, employees, and students, to strengthen financial resources for sustainable community-based economic growth.